La inmigración docente como posibilidad histórica: el caso de la Universidad Nacional de Colombia, 1930 - 1950 - Silva, Renán (Sociedad y Economía, 2008)
Colombian intellectual culture of the twentieth century has an enormous debt with European teachers and researchers who came to the country fleeing from Nazism and Fascism. Highlights of this process are studied in this paper, which considers the case of Colombia´s main university through new sources taken from the archives of that institution.